2019
DOI: 10.1186/s10033-019-0364-4
|View full text |Cite
|
Sign up to set email alerts
|

Micro Model of Carbon Fiber/Cyanate Ester Composites and Analysis of Machining Damage Mechanism

Abstract: Machining damage occurs on the surface of carbon fiber reinforced polymer (CFRP) composites during processing. In the current simulation model of CFRP, the initial defects on the carbon fiber and the periodic random distribution of the reinforcement phase in the matrix are not considered in detail, which makes the characteristics of the cutting model significantly different from the actual processing conditions. In this paper, a novel three-phase model of carbon fiber/cyanate ester composites is proposed to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The milling force of 45°/135° fiber direction laminate is smaller than that of 0°/90° fiber direction laminate. The location of the maximum tangential force is matched with the area generated by delamination [39]. Machining surface damage mainly includes hole defects caused by local single carbon fiber fracture, surface cracks caused by elastic bending deformation of carbon fiber, and voids or incomplete adhesion between carbon fiber and matrix.…”
Section: Materials Removal Mechanismmentioning
confidence: 99%
“…The milling force of 45°/135° fiber direction laminate is smaller than that of 0°/90° fiber direction laminate. The location of the maximum tangential force is matched with the area generated by delamination [39]. Machining surface damage mainly includes hole defects caused by local single carbon fiber fracture, surface cracks caused by elastic bending deformation of carbon fiber, and voids or incomplete adhesion between carbon fiber and matrix.…”
Section: Materials Removal Mechanismmentioning
confidence: 99%
“…Li et al [12] discussed the damage behaviors of UD-CFRP in single-and multiple-pass strategies orthogonal cutting by combining the FE models and the experiments. Liu et al [13] proposed a novel three-phase nite element model of CFRP to simulate the machining damages. Cheng et al [14] revealed the deformation mechanism of UD-CFRP by building the micro-scale thermal-mechanical coupling numerical simulation model.…”
Section: Introductionmentioning
confidence: 99%